Using powdered fallen leaves as organic fertilizer (plant compost) as an alternative to chemical fertilizers (مجلة العلوم الشاملة, 2026)
A pots experiment was conducted in the city of Tobruk during the 2024/2025 season, where fallen green leaves from trees were collected from multiple places, cleaned, then ground into a fine powder and mixed with the soil before planting the bean plant (Vicia faba), El-Kobrosy cultivar. The treatments were arranged in a design Randomized complete block (RCBD), with three replicates. The studied traits included vegetative traits (plant height, total fresh weight, number of branches/ plant, average leaf area, total chlorophyll), yield traits (number of pods/ plant, number of seeds/ pod, pod weight, weight of 100 seeds), chemical content (nitrogen, phosphorus, potassium, protein, total carbohydrates). The results showed that increasing the rate of adding green manure powder to the soil, 300g/2 kg of soil, led to a significant increase in all vegetative traits (plant height, total fresh weight, number of branches/plant, average leaf area, total chlorophyll) and crop traits (number of pods/plant). Number of seeds/pod, weight of pod, weight of 100 seeds), chemical content (nitrogen, phosphorus, potassium, protein, total carbohydrates), followed by the rate of adding green manure powder to the soil, 200 g/ 2kg of soil, compared with the control treatment (without addition), which recorded the lowest values ​​for all the studied traits. We conclude from the previous results that the powder of ground green leaves (green manure) proved effective on all the studied traits due to its positive effect on the physical and chemical properties of the soil, and this was reflected in recording the highest moral values ​​for all the studied traits, while the positive control outperformed the negative control, recording relatively higher values.